Inside Rebellion The Politics of Insurgent Violence - Weinstein, Jeremy M (Cambridge University Press, 2013)
Word of the rebels came first in the form of rumors. “There are men who move at night,” he was told. “They live deep in the forest.” “They are strangers to this zone.” But Samuel had never seen them with his own eyes.1 Government soldiers, however, were known to Samuel and his neighbors. They came in packs, demanding to know where the guerrillas were hiding. Out of fear, people would sometimes offer information. Samuel recalled one person who volunteered to take government soldiers to a rebel camp. They shot him from behind as he led them into the forest. The government troops claimed he was plotting to have them ambushed.